The types of marine biota that live in the mangrove ecosystem, in the village of Kombot, South Bolaang Mongondow Regency - Ogin Sutanto Mokoagow; Tiara Septiani Lawadjo (Fisheries and Society Publisher, 2021)
Mangrove ecosystem is a transitional ecosystem between land and sea or with waters around river mouths. In the mangrove habitat there is at least one life cycle of various species of fish and invertebrates. Primary production in the waters around the mangroves is quite high for water fertility. Leaves, twigs, flowers, and other parts of the mangrove are utilized by macrofauna, such as crabs and then decomposed by various types of microbes attached to the bottom of the water and together form a food chain. The detritus is then utilized by various aquatic animals, therefore the mangrove ecosystem is an important habitat for marine organisms. The purpose of writing this article is to provide information and knowledge for readers about the types of marine biota that live in the mangrove ecosystem, which is located in Kombot Village, Pinolosian District, South Bolaang Mongondow Regency.